2023
DOI: 10.1001/jamainternmed.2023.0015
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cardiovascular Health With Life Expectancy Free of Cardiovascular Disease, Diabetes, Cancer, and Dementia in UK Adults

Abstract: ImportanceThe average life expectancy has increased substantially in the past few decades in most industrialized countries; however, not all of the increased life expectancy is being spent in optimal health, especially among individuals with low socioeconomic status.ObjectiveTo quantify the associations between levels of cardiovascular health (CVH), estimated by the American Heart Association’s Life’s Essential 8 (LE8) metrics, with life expectancy free of major chronic disease, including cardiovascular diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…LE8 is the American Heart Association's updated and enhanced guideline to measure and promote CVH for individuals and populations 3 . The beneficial associations of following the LE8 with lower risks of CHD, CVD, and related mortality have been demonstrated in recent studies [4][5][6][7] . However, multi-racial/ethnic populations with low SES remain underrepresented in research studies, even though they have persistently experienced worse CVH and CVD outcomes, as well as systemic disadvantages to improve CVH, than White and middle-class Americans 2,41-43 .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…LE8 is the American Heart Association's updated and enhanced guideline to measure and promote CVH for individuals and populations 3 . The beneficial associations of following the LE8 with lower risks of CHD, CVD, and related mortality have been demonstrated in recent studies [4][5][6][7] . However, multi-racial/ethnic populations with low SES remain underrepresented in research studies, even though they have persistently experienced worse CVH and CVD outcomes, as well as systemic disadvantages to improve CVH, than White and middle-class Americans 2,41-43 .…”
Section: Discussionmentioning
confidence: 84%
“…LE8 includes 4 health behaviors (healthy diet, participation in physical activity, avoidance of nicotine, and healthy sleep [a new component of LE8]) and 4 health factors (weight, blood lipids, glucose, and blood pressure), and has a new scoring system with continuous scale to better reflect inter-individual differences. While a higher LE8 score has been recently associated with lower CVD incidence and mortality [4][5][6][7] , few studies have evaluated LE8 score and its association with incident CVD among Black and White Americans who have low socioeconomic status (SES) and face disproportionate CVD burdens. In addition, although some potential mechanisms have been identified (e.g., reduced inflammation and atherosclerosis) 8,9 , beyond those known CVD risk pathways, mechanisms and interindividual differences underlying the cardioprotective effects of LE8 and its included health behaviors and health factors are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…17 Yet another cohort study involving more than 135,000 adults reported that higher scores on the American Heart Association's Life Essential 8 (an index of cardiovascular health) were associated with a longer life expectancy free from major chronic diseases (ie, cardiovascular disease, cancer, diabetes, and dementia). 18 While value-based care models are gathering momentum 9 and have the potential to promote heavier emphasis on Lifestyle as Medicine, 19 there is a critical role for employers to play. And employers may be uniquely suited for championing Lifestyle as Medicine.…”
mentioning
confidence: 99%
“…In the Original Investigation titled “Association of Cardiovascular Health With Life Expectancy Free of Cardiovascular Disease, Diabetes, Cancer, and Dementia in UK Adults,” published online February 27, 2023, several of the bars in the graph of Figure 1 were reported incorrectly. Additionally, eFigures 4 and 5 were missing in Supplement 1.…”
mentioning
confidence: 99%